2010
DOI: 10.4088/jcp.09m05282blu
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Treatment With Escitalopram of Pegylated Interferon Alfa-2a–Induced Depression in Hepatitis C

Abstract: clinicaltrials.gov Identifier: NCT00166296.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Instrument (3): Self efficacy scale: This scale was developed by [24] to measure self-efficacy of chronic ill patients. It was translated into Arabic and tested for its content validity and reliability by the researcher and it consists of 21 items in the form of likart scale, at point ranged from (1) to (10) (not at all confident take score (1) to totally confident take score (10). This scale divided into 3 items related to confidence in doing regular exercises, one item related to confidence on getting information about disease, 4 items related to confidence about obtaining help from community and friends, 3 items related to confidence on communication with physician, 5 items related to confidence on managing disease in general, 3 items related to confidence on doing chores, 2 items related to confidence on social and recreational activity, 1 item related to managing shortness of breathing The scoring system for total selfefficacy was less than 165 mean low self-efficacy, score from 165 to 215 mean mild self-efficacy, score from 216 to 281 mean moderate self-efficacy and score from 282 to 330 mean high self-efficacy.…”
Section: Instruments Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument (3): Self efficacy scale: This scale was developed by [24] to measure self-efficacy of chronic ill patients. It was translated into Arabic and tested for its content validity and reliability by the researcher and it consists of 21 items in the form of likart scale, at point ranged from (1) to (10) (not at all confident take score (1) to totally confident take score (10). This scale divided into 3 items related to confidence in doing regular exercises, one item related to confidence on getting information about disease, 4 items related to confidence about obtaining help from community and friends, 3 items related to confidence on communication with physician, 5 items related to confidence on managing disease in general, 3 items related to confidence on doing chores, 2 items related to confidence on social and recreational activity, 1 item related to managing shortness of breathing The scoring system for total selfefficacy was less than 165 mean low self-efficacy, score from 165 to 215 mean mild self-efficacy, score from 216 to 281 mean moderate self-efficacy and score from 282 to 330 mean high self-efficacy.…”
Section: Instruments Of the Studymentioning
confidence: 99%
“…Antidepressant medications have been the most readily available therapeutic option for HCV specialists to manage their patients' emotional distress. However, the evidence demonstrating the efficacy of antidepressants in ameliorating IFN-induced depression is equivocal [10] and [11]. Pharmacotherapy also has limitations (e.g., patient reluctance due to side effects, addiction history, and liver toxicity) and does not build self-efficacy or coping skills to empower patients to self-manage symptoms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diez-Quevedo et al [14] in their randomized, multicenter, double-blind, placebo-controlled study of escitalopram in the prophylaxis of interferon-induced depression during the first 12 weeks of treatment of 133 patients with chronic hepatitis C did not find any statistical difference between escitalopram and placebo (the rates of major depression were 3.2% with placebo and 7.6% with escitalopram). The results of this study suggest that the practice of prophylaxis of interferon-induced depression with antidepressants is not warranted.…”
Section: Antidepressants Reevaluatedmentioning
confidence: 99%
“…The articles [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22] are presented in groups according to similarity of their topic, not in any order of importance, preference or significance.…”
mentioning
confidence: 99%
“…In contrast to other reports, it did not result in less depression compared to placebo; however, a longer follow-up may have yielded different results, since other studies have demonstrated peak of depression after the 12th week of treatment. 68 Milnacipran, a serotonin and norepinephrine re-uptake inhibitor (SNRI), was studied in elderly depressed patients on IFN and was found to be efficacious with no incidence of anticholinergic or other side effects. 69 Of note, the use of tricyclic antidepressants probably should be avoided, because of increased sedation and worsened cognition, potentiation of the side effects of IFN, and possible cardiotoxicity.…”
Section: Prevention and Treatment Of Ifn-induced Depressionmentioning
confidence: 99%